INCREASING TRANSPARENT SOAP PRODUCTION BY UTILIZING VIRGIN COCONUT OIL (VCO) AND ORANGE PEEL EXTRACTTO INCREASE ANTIOXIDANT PROPERTIES - Hestina; Gultom, Erdiana; Zai, Liver Iman Putra; Mendrofa, Yelsin Alfidar (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2023)
Orange peel may be a plant that produces fundamental oils that are utilized as cancer prevention agents. Straightforward soap is one of the cleanser innovations that creates cleanser more alluring and includes a smoother froth. In this ponder utilizing the refining strategy to get fundamental oil extricates from orange peels. At that point, in this ponder utilizing virgin coconut oil as an fixing in making cleanser, where virgin coconut oil (VCO) is an oil determined from coconut starch quintessence containing tall lauric corrosive which serves to smooth and moisturize the skin.  The examination conducted in this think about was the investigation of water substance, cleanser pH, tall froth, free antacid, cancer prevention agents, and FTIR. The strategy utilized in analyzing antioxidant movement in this think about is the DPPH strategy. In this ponder, water substance was gotten as much as 18%, 26%, 28%, and 30%. The pH esteem in this consider contains a esteem of 8 and free soluble base test values were gotten at 0.2%, 0.3%, 0.2% and 0.1%. For the test esteem of antioxidant action of basic oils gotten by 63.95%, in straightforward cleanser with the expansion of fundamental oils gotten by 64.14%, in straightforward cleanser without the expansion of basic oils gotten by 45.23%. For tall yields froth is gotten on normal 7 cm. The esteem of pH and free antacid substance in this think about has met the Indonesian National Standard (SNI) for straightforward strong cleanser.